2022
DOI: 10.1186/s12902-022-01245-7
|View full text |Cite
|
Sign up to set email alerts
|

Association of cardiometabolic risk factors with insulin resistance in overweight and obese children

Abstract: Introduction Regarding the increased prevalence of obesity among children and adolescents, and the impact of obesity on insulin resistance (IR) and other metabolic disorders, this study was performed to determine the association of cardiometabolic risk factors (CMRFs) with IR in overweight and obese children. Method In this cross-sectional study 150 overweight and obese children (BMI ≥ 85th and BMI ≥ 95th age-sex specific percentile) and adolescent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 36 publications
0
4
0
Order By: Relevance
“…Waistheight ratio has been proposed by the National Institute for Health and Care Excellence as a better representative of adiposity measure when compared to BMI 47 . It was assessed as a ratio of waist circumference by height, both measurements in centimeters, as a simple screening tool, which holds great potential for diagnosis of early cardiometabolic risk [48][49][50][51][52][53] . The values of the WHtR (de ning the degree of central adiposity) included: a ratio of 0.4 to 0.49, indicating no increased health risks while ratio of 0.5 and above were categorized as suggestive of increased health risks 47,49,53 .…”
Section: Discussionmentioning
confidence: 99%
“…Waistheight ratio has been proposed by the National Institute for Health and Care Excellence as a better representative of adiposity measure when compared to BMI 47 . It was assessed as a ratio of waist circumference by height, both measurements in centimeters, as a simple screening tool, which holds great potential for diagnosis of early cardiometabolic risk [48][49][50][51][52][53] . The values of the WHtR (de ning the degree of central adiposity) included: a ratio of 0.4 to 0.49, indicating no increased health risks while ratio of 0.5 and above were categorized as suggestive of increased health risks 47,49,53 .…”
Section: Discussionmentioning
confidence: 99%
“…The following variables were used as markers for increased cardiometabolic risk: WHtR parameters: There is no consensus on the appropriate cut points of WHtR in pediatric populations [ 15 18 , 20 , 28 ]. Previous reviews and analyses have indicated that dichotomized WHtR cut points at ≥ 0.5 [ 18 ] or 0.55 [ 29 ] are surrogates of increased risk in children; however, they may be insignificant when assessed for sensitivity and specificity to certain variables [ 30 32 ].…”
Section: Methodsmentioning
confidence: 99%
“…Waist-to-height ratio (WHtR), derived as a ratio of waist circumference in centimeters (cms) by height (cms), a simple screening tool [ 13 ], has recently been proposed as a diagnostic measure of early cardiometabolic risk in both children [ 3 , 14 – 16 ] and adults [ 16 19 ]. WHtR is more strongly associated with cardiovascular and cardiometabolic risk factors than individual anthropometric measures, such as waist circumference, Body Mass Index (BMI), and waist-hip ratio [ 15 , 17 , 20 24 ]. [ 21 , 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…Diabetes and prediabetes, which are a continuum of impaired insulin resistance and/or secretion, develop even in adolescents [ 1 ]. Impaired glucose metabolism in adolescents is associated with increased cardiovascular risk [ 2 ]. The influence of dietary behaviors on type 2 diabetes (T2D) incidence has been documented extensively in the literature [ 3 ].…”
Section: Introductionmentioning
confidence: 99%